Literature review of the clinical characteristics of metformin-induced hepatotoxicity - Wang, Chunjiang; Deng, Hongyi; Xu, Yunfei; Liu, Ying (Frontiers in Pharmacology, 2022)
Background: Knowledge of metformin-induced hepatotoxicity is based on case reports. The aim of this study was to investigate the clinical features of metformin-induced hepatotoxicity. Methods: We collected relevant literature on metformin-induced hepatotoxicity published from January 1994 to February 2022 by searching Chinese and English databases. Results: Thirty patients (19 males and 11 females) from 29 articles were included, with a median age of 61 years (range 29, 83). The median time to onset of liver injury was 4 weeks (range 0.3, 648) after metformin administration. Clinical symptoms occurred in 28 patients, including gastrointestinal reactions (56.7%), jaundice (50.0%), fatigue (36.7%), anorexia (23.3%), pruritus (13.3%), dark urine (13.3%) and clay-colored stools (10.0%). Serum alanine transaminase, aspartate transaminase, γ-glutamyl transferase, total bilirubin and alkaline phosphatase were elevated to varying degrees. Liver imaging in 26 patients showed hepatic steatosis (6 cases, 23.1%) and gallbladder wall thickening (11.5%). Liver biopsies from 13 patients showed portal phlebitis (61.5%), cholestatic hepatitis (38.5%), and parenchymal inflammation (38.5%). After metformin discontinuation, liver function returned to normal levels at a median of 6 weeks (range 2, 16). Conclusions: Metformin-induced hepatotoxicity is a rare adverse reaction. Physicians and patients should be alert to metformin-induced hepatotoxicity.